Assessment of Teachers’ Mental Health Literacy: Basis for An Action Plan - Uncad, Cristina; Umali, Jennelyn; Alvarez, Yelena; Manalastas, Angelito (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the mental health literacy (MHL) of teachers at Lagundi-CCL National High School as basis for an action plan. Mental health literacy is essential in education as teachers are often the first to identify and respond to students experiencing psychological distress. Using a mixed-method descriptive-quantitative research design, data were gathered from 31 teachers through an adapted Mental Health Literacy Scale developed by O’Connor and Casey (2015), supplemented by interview guide questions to capture qualitative insights.Findings revealed that the overall mental health literacy of teachers obtained a mean score of 103.65 (SD = 11.80), indicating a moderate level of literacy. Among the six domains, teachers demonstrated higher competencies in knowledge of professional help available and recognition of mental health disorders. They also showed adequate understanding of self-treatment strategies. However, lower scores were observed in attitudes that promote recognition and appropriate help-seeking behavior, as well as knowledge on how to seek mental health information. These findings suggest that while teachers possess foundational knowledge of mental health conditions and services, stigma and limited proactive help-seeking attitudes remain concerns.Qualitative results further revealed several challenges in the implementation of mental health-related initiatives, including lack of training, insufficient support systems, low engagement in professional development activities, and limited alignment of programs with classroom realities. Despite these challenges, all respondents expressed willingness to learn more about mental health, recognizing its importance in improving student well-being and fostering a supportive learning environment.The study concludes that enhancing teachers’ mental health literacy requires structured training programs, improved institutional support systems, and contextualized professional development initiatives. Strengthening these areas can empower teachers to better support learners’ psychological needs and contribute to a more responsive school environment. An action plan is proposed to address identified gaps and promote sustainable mental health literacy development among teachers.
Keywords: Mental Health Literacy, Teachers, Professional Development, School Mental Health, Action Plan, Mixed-Method Research, Educational Well-Being